INTERCULTURAL DIFFERENCE OR THE CONCEPT OF "LACUNA" - Scientific advisor: U. Kholnazarov; M. Abdukarimova (Western European Studies, 2024)
In this article, lacunae appear in the process of verbal and non-verbal communication as an indicator of the level of specific signs, mentality, and characteristics of national culture in the lexicon and ethnography of each nation. This serves to show the differences between languages and cultures, as well as to eliminate obstacles in intercultural communication.
Keywords: lacuna; unparalleled word; untranslatable lexicon; cultural component